Analisis Indeks Pencemaran (IP) Sungai Konaweha Akibat Pengaruh Aktifitas Tambang Nikel di Kabupaten Konawe, Sulawesi Tenggara - M. Ichsan Ali; Muh. Rais Abidin; Suarlin Suarlin (Seminar Nasional LP2M UNM, 2019)
Indonesia is one of the gifted countries with abundant natural resources in many sectors such as plantation, fishery, agriculture and maining. In order to support the rapid population development, the natural resources are exploited massively to fulfill the needs of human. As a result of this massive exploitation, the environmental degradation could not be avoided such as air, soil and water pollution. Virtue Dragon Nickel Industry, located in Konaweha watershed, indicates polluted the water in the Konaweha river. Therefore, this study aims to identifiy the pollution index water of Konaweha River through physical and chemistry parameter as well as to recommend river management system. Sampling was taken in 2 places in river which was first around the settlement and second around maining industry. Sampling analysis unduwent in laboratory and Pollution Index (PI) was used to identify the level of pollution. The result shows that the highest pollution index is in location 1 located near the maining industry which is 7.20 PI and has moderate pollution level. This happens because in the location 1, the industrial disposal going to the river and also the human activities such as agriculture, plantation and illegal sand mining. Meanwhile, in the location 2 has lower index pollution at 5.40 PI. This is because in location 2, the main source of pollution come from human activities such as agriculture, plantation and illegal sand mining.